The oleoresin secretory system in seedlings and adult plants of copaiba (Copaifera langsdorffii Desf., Leguminosae-Caesalpinioideae) - Rodrigues, Tatiane Maria [UNESP]; Teixeira, Simone de Padua; Machado, Silvia Rodrigues [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
The ecological and economic importance of oleoresin produced by Copaifera langsdorffii is well established. This study aims to investigate the ontogeny, anatomy and ultrastructure of the internal glands of C. langsdorffii during plant development. Samples were processed for light and electron microscopy and a specific technique was applied to impregnate endomembranes. Internal secretory glands were observed in the hypocotyl, epicotyl and eophylls of seedlings, and in the primary stem, pulvinus, petiole, rachis and leaf blade of adult plants. Canals and cavities show differential distribution. They arise from ground meristem cells, and the lumen is first formed by schizogenesis followed by later schizolysigenous development. The dense cytoplasm of epithelial cells shows mitochondria, plastids without thylakoids, polyribosomes and endoplasmic reticulum. A periplastidial reticulum was also observed. Secretion is released by eccrine, granulocrine and holocrine processes. Lipophilic and hydrophilic compounds were histochemically detected in both canals and cavities, whereas resin was detected only in canals. The presence of these substances has been associated with plants' defences against dehydration, as well as against attacks from herbivores and pathogens, from seedling stage onwards. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Anatomy; Canal; Cavity; Copaifera langsdorffii; Ultrastructure